Current research on pycnodysostosis - DEMİRCİOĞLU, SERAP (My University, 2014)
Pycnodysostosis is a rare autosomal recessive disorder caused by an inactivating mutation in cathepsin K (CTSK) and characterized by dysmorphic facial features, a short stature, acroosteolysis, osteosclerosis with increased bone fragility, and delayed closure of cranial sutures. Patients usually present with short stature or dysmorphic features the Pediatric Endocrinology or Genetics clinics, with atypical fractures to the orthopedics clinics or hematological abnormalities to the hematology clinics. However, under-diagnosis or misdiagnosis of this condition is a major issue. Pycnodysostosis is not a life threatening condition, but craniosynostosis, frequent fractures, respiratory-sleep problems, and dental problems may cause significant morbidity. Although no specific treatment for this disorder has been described, patients should be followed for complications and treated accordingly. A specific treatment for the disorder must be established in the future to prevent complications and improve quality of life for patients in the current era of advanced molecular research.
Keywords: cathepsin K; osteopetrosis; Pycnodysostosis